English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. -4, 7
b. -14, 2
c. -7, 4
d. -2,14

2007-01-26 09:10:11 · 6 answers · asked by lana l 1 in Science & Mathematics Mathematics

6 answers

x ^ 2 - 3x = 28

x ^ 2 - 3 x - 28 = 0

( x + 4 ) ( x - 7 ) = 0

x + 4 = 0, x - 7 = 0

x = - 4, x = 7

2007-01-26 09:20:20 · answer #1 · answered by meli409 4 · 1 0

First: set the equation to "0" > subtract "28" from both sides (when you move a variable/term to the opposite side, always use the opposite sign)...

x^2 - 3x - 28 = 28 - 28
x^2 - 3x - 28 = 0

Sec: factor the expression. multiply the 1st & 3rd coefficient to get "-28." Find two numbers that give you "-28" when multiplied & "-3" (2nd/middle coefficient) when added/subtracted. The numbers are: "-7 and 4"....

*Rewrite the expression with the new middle coefficients...

x^2 - 7x + 4x - 28 = 0

*When you have 4 terms, group "like" terms & factor...

(x^2 - 7x) + (4x - 28) = 0
x(x - 7) + 4(x - 7) = 0
(x - 7)(x + 4) = 0

Third: solve the two x-variables > set both parenthesis to "0"...

a. x - 7 = 0 > *Add "7" to both sides...
x - 7 + 7 = 0 + 7
x = 7

b. x + 4 = 0 > *Subtract "4" from both sides...
x + 4 - 4 = 0 - 4
x = - 4

Solutions: 7 and - 4

2007-01-26 10:50:52 · answer #2 · answered by ♪♥Annie♥♪ 6 · 1 0

x² - 3x = 28
=> x² - 3x - 28 = 0
=> x² -7x + 4x - 28 = 0
=> x (x - 7) + 4 (x - 7) = 0
=> (x + 4) (x - 7) = 0
=> x = -4, x = 7 (Option A)

2007-01-26 09:23:36 · answer #3 · answered by Anonymous · 1 0

x^2-3x -28 = 0, collect all terms in one side
(x-7)(x+4) = 0, factor
x = -4, 7, solve each factor = 0 for x

2007-01-26 09:20:38 · answer #4 · answered by sahsjing 7 · 1 0

The answer is a.
x^2-3x=28
x^2-3x-28=0
(x-7)(x+4)=0
x-7=0
x=-7

x+4=0
x=-4

2007-01-26 09:22:27 · answer #5 · answered by elise_dreamer_95 2 · 0 1

x^2-3x-28=0
(x+4)(x-7)=0
x=-4 , 7
a is correct

2007-01-26 09:48:08 · answer #6 · answered by Calvin N 1 · 1 0

fedest.com, questions and answers